DATASET "De-icer Mobilisation by Rainfall" - Exton, Benjamin; Grabowski, Robert C. (Cranfield University, 2024)
HPLC data of propylene glycol in runoff (mobilised de-icer in rainfall)
Keywords: airport de-icer; airport anti-icer; runoff; mobilisation; transport mechanisms